Evaluación del potencial natural de los paisajes para la actividad agropecuaria en el ejemplo del municipio de Yaguajay (provincia Sancti-Spiritus, Cuba) - Arceo Kindelán, Sara; Salinas Chávez, Eduardo (Geographicalia, 2017)
This article tries to show the advantages of the studies of integrated landscape and the determination of their natural resources in territorial management in Cuba.